Sourcing methane and carbon dioxide emissions from a small city: Influence of natural gas leakage and combustion. (November 2016) - Chamberlain, Samuel D.; Ingraffea, Anthony R.; Sparks, Jed P.
Abstract: Natural gas leakage and combustion are major sources of methane (CH4 ) and carbon dioxide (CO2 ), respectively; however, our understanding of emissions from cities is limited. We mapped distribution pipeline leakage using a mobile CH4 detection system, and continuously monitored atmospheric CO2 and CH4 concentrations and carbon isotopes (δ 13 C-CO2 and δ 13 C-CH4 ) for one-year above Ithaca, New York. Pipeline leakage rates were low (<0.39 leaks mile −1 ), likely due to the small extent of cast iron and bare steel within the distribution pipeline system (2.6%). Our atmospheric monitoring demonstrated that the isotopic composition of locally emitted CO2 approached the δ 13 C range of natural gas combustion in winter, correlating to natural gas power generation patterns at Cornell's Combined Heat and Power Plant located 600 m southeast of the monitoring site. Atmospheric CH4 plumes were primarily of natural gas origin, were observed intermittently throughout the year, and were most frequent in winter and spring. No correlations between the timing of atmospheric natural gas CH4 plumes and Cornell Plant gas use patterns could be drawn. However, elevated CH4 and CO2 concentrations were observed coincident with high winds from the southeast, and the plant is the only major emission source in that wind sector. Our results demonstrate pipeline leakage rates are low in cities with a low extent of leak prone pipe, and natural gas power facilities may be an important source of urban and suburban emissions. Graphical abstract: Highlights: Quantification of CO2 and CH4 emissions from a small city across time and space. Low pipeline leakage rates are likely due to few cast iron distribution pipelines. Atmospheric monitoring records intermittent natural gas CH4 emissions from Ithaca. Atmospheric CO2 isotope values correlate to natural gas use at nearby power plant. High CO2 and CH4 concentrations observed on winds from power plant's direction. Abstract : This work provides a comprehensive quantification of CO2 and CH4 dynamics across time and space and demonstrates that power plants may be an important source of urban emissions.